2017
DOI: 10.1186/s13046-017-0605-2
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stromal cells as cellular drug-delivery vectors for glioblastoma therapy: a good deal?

Abstract: BackgroundGlioblastoma (GB) is the most malignant brain tumor in adults. It is characterized by angiogenesis and a high proliferative and invasive capacity. Standard therapy (surgery, radiotherapy and chemotherapy with temozolomide) is of limited efficacy. Innovative anticancer drugs targeting both tumor cells and angiogenesis are urgently required, together with effective systems for their delivery to the brain. We assessed the ability of human mesenchymal stromal cells (MSCs) to uptake the multikinase inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 62 publications
0
27
0
7
Order By: Relevance
“…An HPLC-UV method was used to quantify SFN, as previously described (Clavreul et al., 2017 ). Briefly, HPLC was performed on a Waters modular system (600/717/996/2414) (Waters, Saint-Quentin-en-Yvelynes, France) with a SunFire ® C18 column (150 × 4.6 mm; 5 μm) at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An HPLC-UV method was used to quantify SFN, as previously described (Clavreul et al., 2017 ). Briefly, HPLC was performed on a Waters modular system (600/717/996/2414) (Waters, Saint-Quentin-en-Yvelynes, France) with a SunFire ® C18 column (150 × 4.6 mm; 5 μm) at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…A specific LC-MS/MS method was previously developed (Clavreul et al., 2017 ). Briefly, chromatography was performed on a Waters Alliance ® 2695 system with an Uptisphere ® 5 0DB (150 × 2.0 mm) column, at 25 °C, using an isocratic mixture of 0.1% formic acid in water/0.1% formic acid in acetonitrile: 20/80 (v/v) at a flow rate of 0.3 mL/min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated that MSCs promote angiogenesis by secreting angiogenic factors, such as VEGF, releasing exosomes, recruiting endothelial progenitors, and/or transdifferentiating into endothelial cells. 104,105 Our previous studies 96,106 showed no effect of unprimed MSCs on tumor volume or the proportion of Ki67 + tumor cells in the human U87MG GB model, but MSCs have been reported to facilitate tumor growth by secreting various anti-inflammatory cytokines and proangiogenic factors. [100][101][102][103] Furthermore, MSCs can differentiate into cancer-associated fibroblasts (CAFs), which have been detected in the stroma of carcinomas and are known to promote tumor growth.…”
Section: Adult Stem Cellsmentioning
confidence: 99%
“…We recently showed that MSCs can deliver the chemotherapy drug ferrociphenol and the antiangiogenic TKI SFN to brain tumors without the need for genetic modification. 95,96 MSCs can be primed in vitro with SFN, with no effect on viability, and can release 60% of the drug with which they are loaded. The cytostatic activity of the released SFN was entirely conserved, significantly decreasing the survival of human U87MG GB cells and endothelial cells in vitro.…”
Section: Adult Stem Cellsmentioning
confidence: 99%